Rock art and social networks among hunter gatherers of north-central Chile - (:unkn) unknown (Elsevier, 2016)
This paper discusses the relationships between rock art and the production of social networks among hunter-gatherers from the Late Holocene in central-northern Chile. Despite the low visual integrity of the paintings under study, the use of D-Stretch software allowed us to digitally improve the images, and conduct formal and quantitative analyses at different levels of variability. The comparison between two areas of the region showed two systems of visual communication that structure themselves along divergent principles. Such results point to the existence of two different social network systems due to social complexity processes and the increasing spatial demands of the communities living in the area. The very existence of rock art is interpreted in the light of these historical processes. The results we present help expanding the discussion on rock art and social networks considering the multiscalar nature of the networks as well as by weighing the role of history and environment in such a process.

Troncoso, A., Moya, F. y Basile, M. V. (2016). Rock art and social networks among hunter gatherers of north-central Chile. Journal of Anthropological Archaeology, 42, 154-168.
Fil: Troncoso, Andrés. Universidad de Chile. Departamento de Antropología; Chile
Fil: Moya, Francisca. Universidad de Chile; Chile
Fil: Basile, Mara Valeria. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina
Keywords: Rock art; Social networks; Social complexity; Hunter gatherers; D-Stretch; Chile